Blockchain basics : a non-technical introduction in 25 steps - Drescher, Daniel (Berkeley, California : Apress, 2017)
In 25 concise steps, you will learn the basics of blockchain technology. No mathematical formulas, program code, or computer science jargon are used. No previous knowledge in computer science, mathematics, programming, or cryptography is required. Terminolog is explained through pictures, analogies, and metaphors. This book bridges the gap that exits between purely technical books about the blockchain and purely business-focused books. It does so by explaining both the technical concepts that make up the blockchain and their role in business-relevant applications.
Stage 1. Terminology and technical foundations -- Stage 2. Why the Blockchain is needed -- Stage 3. How the Blockchain works -- Stage 4. Limitations and how to overcome them.
Includes index.
Keywords: Blockchains (Databases).; Electronic funds transfers; Database management; Electronic commerce; Data encryption (Computer science).